Minimally Invasive Approach for Dorsal Arachnoid Web: 2-Dimensional Operative Video. Issue 6 (25th August 2021) - Dauleac, Corentin; Leroy, Henri-Arthur; Assaker, Richard
Abstract: A 67-yr-old patient presented with severe paraparesis and lower limb spasticity. The spinal cord magnetic resonance imaging (MRI) revealed the "scalpel sign"  1, 2 at the T7 level, suggesting a diagnosis of a dorsal arachnoid web. This video demonstrates a microsurgical technique for the excision of a dorsal arachnoid web with a minimally invasive approach. A paramedian skin incision, understanding the muscular aponeurosis, was performed from T7 to T8. Then, we inserted the tubular dilators until the lamina, to perform a muscle-sparing approach. An expandable tubular retractor of adequate length was passed over the widest dilator and docked into place along the subperiosteal plane. The T7 lamina was drilled, and the resection of the superior and inferior adjacent spine levels was completed with a rongeur. Additional contralateral bone resection was performed after tubular retractor tilt to the midline. 3 After dura mater opening, it was carefully suspended and the dorsal arachnoid leaflet was cut to drain the dorsolateral and lateral spinal cisterns. 4 The dorsal arachnoid web was, first, disconnected from its lateral anchorages. It was then gently removed with microsurgical forceps, to help its microdissection from the spinal cord surface. At this step, peculiar attention was paid to limit the traction or displacements of the spinal cord and surrounding vessels. Once the dorsal arachnoid web was removed, the quality of the spinal cord decompression was confirmed by its re-expansion. In conclusion, the minimally invasive approach is a safe and appropriate technique for dorsal arachnoid web excision. 2, 5, 6-7  The patient gave her informed and signed consent for the writing and publication of this article.  Image at 1:00 reused with permission from Castelnovo G et al, Spontaneous transdural spinal cord herniation, Neurology, 2014;82(14):1290.